160k views
4 votes
2x2 – 5x + 67 = 0

What would be your first step in completing the square for the equation above?

1 Answer

1 vote

Answer:

The first step is to divide all the terms by the coefficient of
x^(2) which is 2.

The solutions to the quadratic equation
2x^2\:-\:5x\:+\:67\:=\:0 are:


x=(5)/(4)+i(√(511))/(4),\:x=(5)/(4)-i(√(511))/(4)

Explanation:

Considering the equation


2x^2\:-\:5x\:+\:67\:=\:0

The first step is to divide all the terms by the coefficient of
x^(2) which is 2.

so


(2x^2-5x)/(2)=(-67)/(2)


x^2-(5x)/(2)=-(67)/(2)

Lets now solve the equation by completeing the remaining steps

Write equation in the form:
x^2+2ax+a^2=\left(x+a\right)^2

Solving for
a,


2ax=-(5)/(2)x


a=-(5)/(4)


\mathrm{Add\:}a^2=\left(-(5)/(4)\right)^2\mathrm{\:to\:both\:sides}


x^2-(5x)/(2)+\left(-(5)/(4)\right)^2=-(67)/(2)+\left(-(5)/(4)\right)^2


x^2-(5x)/(2)+\left(-(5)/(4)\right)^2=-(511)/(16)

Completing the square


\left(x-(5)/(4)\right)^2=-(511)/(16)

Since, you had required to know the first step in completing the square for the equation above, I hope you have got the point, but let me quickly solve the remaining solution.

For
f^2\left(x\right)=a the solution are
f\left(x\right)=√(a),\:-√(a)

Solving


x-(5)/(4)=\sqrt{-(511)/(16)}


x-(5)/(4)=√(-1)\sqrt{(511)/(16)}


x-(5)/(4)=i\sqrt{(511)/(16)} ∵ Applying imaginary number rule
√(-1)=i


x-(5)/(4)=i(√(511))/(√(16))


-(5)/(4)=i(√(511))/(4)


x=(5)/(4)+i(√(511))/(4)

Similarly, solving


x-(5)/(4)=-\sqrt{-(511)/(16)}


x-(5)/(4)=-i(√(511))/(4) ∵ Applying imaginary number rule
√(-1)=i


x=(5)/(4)-i(√(511))/(4)

Therefore, the solutions to the quadratic equation are:


x=(5)/(4)+i(√(511))/(4),\:x=(5)/(4)-i(√(511))/(4)

User Douglasrcjames
by
6.0k points